Viability of Entomopathogenic Fungi Metarhizium anisopliae (Metsch) Sorokin in Some Alternative Media and Different Shelf-Life - Lutfi Afifah; Rizky Desriana; Anik Kurniati; Rosalia Maryana (Hasanuddin University, 2020)
Pest control by using chemical pesticides continuously can harm the environment. Therefore it is necessary to look for environmentally friendly technologies, one of which is the use of entomopathogenic fungi such as Metarhizium anisopliae. The alternative media should be easy to obtain and has a good shelf life so the growth of M. anisopliae should be optimum. This research aimed to obtain alternative media that provide the best growth and development at each different shelf-life. The research method used was an experimental method using a Completely Randomized Design (CRD) Factorial and it was repeated 4 times. The media factors were from PDA, bran, green beans, and maize. The shelf-life factors were at 21 and 42 days old (d-old). The diameter on maize media gave the highest diameter value of 8.57 cm at 42 d-old. Green bean media gave the best spore density results of 2.08×107. Whereas the germination capacity of the media ranged from 63.94% to 94.23%. Germination showed no significant difference at 21 and 42 d-old. Therefore, green beans and maize media were effectively used for propagation of M. anisopliae as a substitute for synthetic media.